`NMR Crystallization': in‐situ NMR techniques for time‐resolved monitoring of crystallization processes. Issue 3 (6th February 2017) - Harris, Kenneth D. M.; Hughes, Colan E.; Williams, P. Andrew; Edwards-Gau, Gregory R.
Abstract : A number of technical challenges are associated with adapting solid‐state NMR spectroscopy for in‐situ studies. Recently, an in‐situ solid‐state NMR strategy for monitoring the evolution of crystallization processes has been developed and has proven to be a promising approach for identifying the sequence of distinct solid forms present as a function of time during crystallization from solution, and for the discovery of new polymorphs. The latest development of this technique, called `CLASSIC' NMR, allows the simultaneous measurement of both liquid‐state and solid‐state NMR spectra as a function of time, thus yielding complementary information on the evolution of both the liquid phase and the solid phase during crystallization from solution. Abstract : Solid‐state NMR spectroscopy is a well‐established and versatile technique for studying the structural and dynamic properties of solids, and there is considerable potential to exploit the power and versatility of solid‐state NMR for in‐situ studies of chemical processes. However, a number of technical challenges are associated with adapting this technique for in‐situ studies, depending on the process of interest. Recently, an in‐situ solid‐state NMR strategy for monitoring the evolution of crystallization processes has been developed and has proven to be a promising approach for identifying the sequence of distinct solid forms present as a function of time during crystallization from solution, and for the discovery of new polymorphs. The latest development of this technique, called `CLASSIC' NMR, allows the simultaneous measurement of both liquid‐state and solid‐state NMR spectra as a function of time, thus yielding complementary information on the evolution of both the liquid phase and the solid phase during crystallization from solution. This article gives an overview of the range of NMR strategies that are currently available for in‐situ studies of crystallization processes, with examples of applications that highlight the potential of these strategies to deepen our understanding of crystallization phenomena.